Effect of cane length and swing arc width on drop-off and obstacle detection with the long cane. (September 2017) - Shik Kim, Dae; Wall Emerson, Robert; Naghshineh, Koorosh
A repeated-measures design with block randomization was used for the study, in which 15 adults with visual impairments attempted to detect the drop-offs and obstacles with the canes of different lengths, swinging the cane in different widths (narrow vs wide). Participants detected the drop-offs significantly more reliably with the standard-length cane (79.5% ± 6.5% of the time) than with the extended-length cane (67.6% ± 9.1%), p  < .001. The drop-off detection threshold of the standard-length cane (4.1 ± 1.1 cm) was also significantly smaller than that of the extended-length cane (6.5 ± 1.8 cm), p  < .001. In addition, participants detected drop-offs at a significantly higher percentage when they swung the cane approximately 3 cm beyond the widest part of the body (78.6% ± 7.6%) than when they swung it substantially wider (30 cm; 68.5% ± 8.3%), p  < .001. In contrast, neither cane length ( p  = .074) nor cane swing arc width ( p  = .185) had a significant effect on obstacle detection performance. The findings of the study may help orientation and mobility specialists recommend appropriate cane length and cane swing arc width to visually impaired cane users.